2021
DOI: 10.1186/s12939-021-01522-2
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in health behaviors: exploring mediation pathways through material conditions and time orientation

Abstract: Background Socioeconomic inequalities in health behaviors have been attributed to both structural and individual factors, but untangling the complex, dynamic pathways through which these factors influence inequalities requires more empirical research. This study examined whether and how two factors, material conditions and time orientation, sequentially impact socioeconomic inequalities in health behaviors. Methods Dutch adults 25 and older self-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…However, the included studies did not control for confounding factors that may have influenced the strength of the association between household income and vaccine willingness including education level and health literacy; ethnicity; access to vaccines and healthcare services; and urban vs rural living to name a few [84][85][86][87]. A Finnish study suggests it may be more appropriate to use the term 'low socio-economic status' rather than 'low household income' to account for the confounding variables that may be contributing to this association [88,89]. Going forward, it would be interesting to further examine the impact that these confounding variables may have had on the association between income and willingness.…”
Section: Comparison To Existing Literaturementioning
confidence: 99%
“…However, the included studies did not control for confounding factors that may have influenced the strength of the association between household income and vaccine willingness including education level and health literacy; ethnicity; access to vaccines and healthcare services; and urban vs rural living to name a few [84][85][86][87]. A Finnish study suggests it may be more appropriate to use the term 'low socio-economic status' rather than 'low household income' to account for the confounding variables that may be contributing to this association [88,89]. Going forward, it would be interesting to further examine the impact that these confounding variables may have had on the association between income and willingness.…”
Section: Comparison To Existing Literaturementioning
confidence: 99%
“…The authors of the scarcity theory [ 71 ] state that scarcity (for example, the scarcity of money) leads to chronic stress and causes a shortage of brainpower and capability to process information, and this shortage, in turn, contributes to scarcity. Experiencing scarcity can impede being able to pay attention, make good decisions, hold on to plans and resist (unhealthy) temptations [ 72 ]. Dynamic feedback loops of this type which can hinder or support the effects of actions and interventions are not shown in the figure with the person, ball and slope.…”
Section: The Complexity Of Changing Health-related Behaviors In Low-s...mentioning
confidence: 99%
“…Subjective SES refers to comparative social standing relative to others and differs from objective measures such as education and income (Natalie H. Brito & Kimberly G. Mudd, van Lenthe, Verra, Bal, & Kamphuis, 2021). Gianaros et al found subjective social status was associated with reduced gray matter volume in the anterior cingulate cortex, a region involved in the regulation of behavioral and physiologic reactions to stress, and not correlated with hippocampal or amygdala volumes (Natalie H. Brito & Kimberly G. .…”
Section: Subjective Sesmentioning
confidence: 99%